VERBAL CARD TO IMPROVE STUDENTS’ WRITING COMPREHENSION IN PASSIVE VOICE - Rini Rismiyati; Rizqiyawati Rizqiyawati; Lies Triatur Nur; Ratno Kumar Jaya (Litbang PWM Jawa Tengah, 2022)
Rini Rismiyati, Rizqiyawati. 2021. Verbal Card to Improve Students’ Writing Comprehension In Passive Voice. Lesson Study, English Education Teacher, SMK Muhammadiyah Kota Pekalongan. This research was conducted under the considerations that tenth grade students of Vocational High School need an interesting strategy in teaching learning process. In this case, this research applied the strategies of learning based on the Verbal Card in teaching writing. In this reserach, the objectives of the study are (1) to know the students’ motivation to learn english, (2) to know the writing comprehension in passive voice of the second grade students of SMK Muhammadiyah Kota Pekalongan who are taught using Verbal Card. This research used quantitative research. The population of this research was the second grade students of SMK Muhammadiyah Kota Pekalongan. The sample of this research was class XI RPL. The instrument of collecting data used by the researcher was a test. The test was post-test. Based on the statistical analysis, the research findings show that (1) there is the students’ motivation to learn english, (2) the writing comprehension in passive voice of the second grade students of SMK Muhammadiyah Kota Pekalongan who are taught using Verbal Card is good. It is shown by the mean of post-test 80.45, Based on the research findings, the researcher suggests that the teacher may use an interesting method in writing class. Teacher can develop his/her students writing skill by using Verbal Card because it proved that Verbal Card is effective to be used to teach writing in passive voice.